A systematic review and meta-analysis of decontamination methods to prevent hospital environmental contamination and transmission of Clostridioidesdifficile. (February 2022) - Kato, Hideo; Hagihara, Mao; Asai, Nobuhiro; Shibata, Yuichi; Yamagishi, Yuka; Iwamoto, Takuya; Mikamo, Hiroshige
Abstract: The current guidelines suggest that hospital rooms previously occupied with Clostridioides difficile infection (CDI) patients should be decontaminated with recommended decontamination methods because C. difficile can persist on surfaces despite adherence to the recommended procedures. Recently, ultraviolet (UV) light and hydrogen peroxide have increasingly been used as innovative decontamination methods. Hence, we conducted a systematic review and meta-analysis to investigate which decontamination methods are effective in reducing environmental C. difficile contamination. We systematically searched the EMBASE, PubMed, CINAHL, Scopus, and Ichushi until March 11, 2021. We evaluated the efficacy of decontamination methods in terms of the frequency of C. difficile contamination on high-touch surfaces in hospital rooms and the incidence of hospital-acquired C. difficile infection. Among the 15 studies retrieved in our meta-analysis, eight evaluated decontamination methods with the frequency of C. difficile detection among samples after disinfection procedures, and eight reported the number of hospital-acquired CDI cases. Pooled analysis indicated that hydrogen peroxide significantly reduced the frequency of environmental C. difficile contamination, compared with hypochlorite (odds ratios [OR]: 0.12; 95% confidence interval [CI]: 0.07–0.23). Additionally, hydrogen peroxide reduced the incidence of hospital-acquired CDI compared to other methods (OR: 0.52; 95% CI: 0.28–0.96). Decontamination with UV significantly reduced the incidence of hospital-acquired CDI compared to hypochlorite (OR 0.52, 95% CI 0.28–0.96). The use of hydrogen peroxide and UV can help prevent environmental C. difficile contamination and transmission in healthcare facilities. Highlights: Compared to hypochlorite, decontamination with hydrogen peroxide in hospital rooms significantly reduced the frequency of environmental Clostridioides difficile contamination. Decontamination with hydrogen peroxide effectively reduced the incidence of hospital-acquired Clostridioides difficile infection, compared to other methods. Ultraviolet light can be an alternative to hypochlorite to prevent hospital-acquired Clostridioides difficile infection.